Penatalaksanaan Holistik Pada Ny. T Umur 56 Tahun dengan Carpal Tunnel Syndrome Melalui Pendekatan Kedokteran Keluarga di Puskesmas Natar - Marga, Muhammad Panji; Zuraida, Reni (Medula, 2024)
Carpal Tunnel Syndrome (CTS) is a clinical syndrome that arises due to the depression of the median nerve in the carpal tunnel (tunnel carpal) on the wrist, which causes pain, numbness, and tingling in the distribution of median nerve. CTS risk factors include obesity, monotonous wrist activity, pregnancy, genetic offspring, and rheumatic inflammation. So it is necessary to handle proper and carried out holistically with a family medicine approach to achieve the success of therapy. The purpose of this study was to implement the service of an evidence-based medicine based family doctor in patients by identifying risk factors, clinical problems, and patient management based on a framework for solving patient problems with the Patient Centered and Family Approach approach. This study is a case report. The data obtained are primary data obtained through autoanamnesis, alloanamnesis, physical examination, and home visits and secondary data obtained from the patient's medical record. Patient Ny. T 56 years old comes with complaints of thumb, index finger, and middle finger of the right hand feels numb since one month ago. Patients also often complain of his fingers feel like shock and spread to the arms, until lately the patient cannot hold or hold objects. Patients work as washerwashers who work daily to wash and make the same movements repeatedly. Clinically the patient is diagnosed with CTS. Furthermore, management, intervention and evaluation are carried out. After holistic and comprehensive management, patients experience increased knowledge about their disease, and complaints of numbness in patients are reduced.